Capital market operations in an emerging economy: the case of Nigeria - Ojo, M.O. (2008)
One of the key challenges facing big businesses is how to secure the huge financing they need to invest in their businesses. From banking, insurance, pharmaceuticals, conglomerates, oil and gas companies and every other sector of the economy, the story is the same. Everyone faces the challenge of funds generation for executing their developmental projects and generally keeping the engine of their businesses running. The government, in a bid to solve this problem, established the Nigerian Securities and Exchange Commission (SEC) as a reliable financial institution where companies could be listed and secure funds to enable them pursue their business plans without going through the banking rituals of looking for collateral securities to get banking loans. To conduct an effective research in this area, therefore, the researcher used a number of research tools, including survey method and the use of questionnaire and interview. This was also backed up with library research to review previous works in the area and thus collect useful data for the work. The findings of the researcher include maintenance of proper regulations on the operations of the Nigerian capital market and ensuring that the interest of investing public is protected. Also the public enlightenment programme by the regulatory authorities evidenced by the daily official trading and weekly summary of trading activities revealed that the authorities have adequately created awareness on the activities of the capital market. The researcher recommends, among other things, strict adherence to the decree and rules that established the Nigerian capital market and the Securities and Exchange Commission. It is also recommended that operators and stakeholders in the capital market should demonstrate a greater display of integrity and transparency now that they have introduced electronic trading or automated trading system, and should ensure proper maintenance of the system.